Does Preendoscopy Rockall Score Safely Identify Low Risk Patients following Upper Gastrointestinal Haemorrhage? - Matthew R. Johnston; Iain A. Murray; Michael Schultz; Peter McLeod; Nathan O’Donnell; Heather Norton; Chelsea Baines; Emily Fawcett; Terry Fesaitu; Hin Leung; Jeong-Yoon Park; Adibah Salleh; et al. (Gastroenterology Research and Practice)
Objective. To determine if preendoscopy Rockall score (PERS) enables safe outpatient management of New Zealanders with upper gastrointestinal haemorrhage (UGIH). Methods. Retrospective analysis of adults with UGIH over 59 consecutive months. PERS, diagnosis, demographics, need for endoscopic therapy, transfusion or surgery and 30-day mortality and 14-day rebleeding rate, and sensitivity and specificity of PERS for enabling safe discharge preendoscopy were calculated. Results. 424 admissions with UGIH. Median age was 74.3 years (range 19–93 years), with 55.1% being males. 30-day mortality was 4.6% and 14-day rebleeding rate was 6.0%. Intervention was required in 181 (46.6%): blood transfusion (147 : 37.9%), endoscopic intervention (75 : 19.3%), and surgery (8 : 2.1%). 42 (10.8%) had PERS = 0 with intervention required in 15 (35.7%). Females more frequently required intervention, OR 1.73 (CI: 1.12–2.69). PERS did not predict intervention but did predict 30-day mortality: each point increase equated to an increase in mortality of OR 1.46 (CI: 1.11–1.92). Taking NSAIDs/aspirin reduced 30-day mortality, OR 0.22 (CI: 0.08–0.60). Conclusion. PERS identifies 10.8% of those with UGIH as low risk but 35.7% required intervention or died. It has a limited role in assessing these patients and should not be used to identify those suitable for outpatient endoscopy.